2016
DOI: 10.3389/fpsyg.2016.00965
|View full text |Cite
|
Sign up to set email alerts
|

Catechol-O-methyltransferase val158met Polymorphism Interacts with Sex to Affect Face Recognition Ability

Abstract: The catechol-O-methyltransferase (COMT) val158met polymorphism affects the breakdown of synaptic dopamine. Consequently, this polymorphism has been associated with a variety of neurophysiological and behavioral outcomes. Some of the effects have been found to be sex-specific and it appears estrogen may act to down-regulate the activity of the COMT enzyme. The dopaminergic system has been implicated in face recognition, a form of cognition for which a female advantage has typically been reported. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The COMT Val/Met (rs4680) polymorphism has been suggested to play a role in face perception [15][16][17][18][19]22 . Our study extends previous findings by identifying a neural site where COMT affects face recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COMT Val/Met (rs4680) polymorphism has been suggested to play a role in face perception [15][16][17][18][19]22 . Our study extends previous findings by identifying a neural site where COMT affects face recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene studies have demonstrated the association of the catechol-O-methyltransferase (COMT) gene, located on chromosome 22q11.2, with face recognition [15][16][17][18][19] . The COMT gene codes for the COMT enzyme, a protein that degrades catecholamine neurotransmitters and modulates dopamine metabolisms 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation